Investigation of the Relationship between Work Ability and Work-related Quality of Life in Nurses - Milad ABBASI; Abolfazl ZAKERIAN; Arash AKBARZADE; Nader DINARVAND; Maryam GHALJAHI; Mohsen POURSADEGHIYAN; Mohammad Hossein EBRAHIMI (Tehran University of Medical Sciences, 2017)
Background: Work ability of nurses is an index of their job satisfaction and is a crucial factor in job quality and security. This study aimed to investigate the association between work ability and quality of working life and to determine the effective demographic and background variables, among nurses. Methods: The present study was conducted among nurses, working in educational hospitals under the supervision of Tehran University of Medical Sciences in 2014. Work Ability Index (WAI) and Work-related Quality of Life (WRQoL) were used. Results: The mean WAI was significantly associated with total WRQoL score and the two of its sub-items including Stress at Work, and General Well-Being (P-value=0.001). Moreover, the results showed a significant correlation between total WRQoL and WAI Subscales including mental resources (P-value=0.001), number of current diseases (P-value=0.02), and work ability in relation to the job demands (P-value=0.04). The WRQoL and WAI showed significant associations with age and job experience (P-value=0.001). The average score of WAI and WRQoL was statistically different among various working units (P-value=0.001).  Conclusion: Overall, results support the association between nurses work ability and WRQoL. Monitoring the WRQoL and work ability of employees would help organizations to know their status and take measures to ameliorate the working conditions.